Fault constitutive relations inferred from the 2009‐2010 slow slip event in Guerrero, Mexico. Issue 14 (23rd July 2014) - Maury, Julie; Aochi, Hideo; Radiguet, Mathilde
Abstract The spatiotemporal evolution of stress state is analyzed during the 2009–2010 Slow Slip Event (SSE) of Guerrero, Mexico, based on the kinematic inversion results and using an integral expression for stress changes. A linear slip weakening behavior is generally observed during the SSE with an average slope of −0.5 ± 0.2MPa/m regardless the perturbation due to the 27 February 2010 Mw = 8.8 Maule, Chile earthquake. This slope remains unchanged before and after the Maule earthquake. However, for some area, the friction behavior changes from slip hardening to slip weakening following the Maule earthquake. The complex trajectory between shear stress and slip velocity is fitted with a rate‐ and state friction law through an inversion. The direct (rate) effect (parameter A) is found to be very small, lower by an order of magnitude than the evolutional (state) effect (parameter B). The characteristic length L is obtained as 5 cm on average.